MUHAMMAD NATSIR’S THOUGHT ON CORRELATION OF RELIGION AND STATE - Wisyly Wahab (JURNAL AL-AQIDAH, 2022)
The wish of Muhammad Natsir  is just how to realize Indonesia as independent, peaceful, prosperous, and just state. So, its logic if he given a nickname as leader of freedom who integrates with the other, Soekarno, in exterminating colonizer – Dutch colonization. Although they are in difference of opinion, but still in building communication each other openly.Muhammad Natsir rejects secularism against state as implemented by movement of Kamal Attaturk in Turkish. He said that Islam is not only merely a religion but also a philosophy of life which covers political aspects, economy, social and culture. Islam doesn’t separate between religion and state, but its primary one. ( D.P. Sati Alimin, 1957: h. IX ) Lesson  of  the  story  can  become  evidence  of  reflection  and  understood  that  in political field the different opinon doesn’t bring enmity, but its mercy and as development of democracy dynamics. Muhammad Natsir consistently refuses all thoughts  that weaken existence of Islam in state such as he opposes Soekarno’s nationalism ideas. This reality is indicated that Muhammad Natsir is a prominent leader of Islam nationalist since the age of Dutch colonization. He is also one of speakers and mediators of his group in verious cases that relate Islam and mankind, namely the correlation between religion and state. Beside that, Natsir’s ability   integrates  His view with his nationalism paradigm, and how then it becomes important one to be studied and thought of its struggle values for next Moslem generation. Actually,  the  above  matter  still  becomes  roof  nowdays.  It  can  be  proven  and indicated by appearing Moslem thinkers and secular thinkers whom they raise voice to fight for their each idea. Even though, deliberation about the correlation of religion and state still can’t be solved untill now. For that reason, this writing is expected as necessary one to be committed.